Is Plasminogen Deficiency a Thrombotic Risk Factor ? – A Study on 23 Thrombophilic Patients and their Family Members - Biasiutti, F. Demarmels; Sulzer, I.; Stucki, B.; Wuillemin, W. A.; Furlan, M.; Lämmle, B. (Thrombosis and Haemostasis, 1998)
The role of plasminogen (plg) deficiency in the pathogenesis of venous thromboembolism is debated in the literature. In the present study we evaluated the prevalence of plg deficiency in our thrombophilia patients and aimed to elucidate the thrombosis risk of plg deficiency as a single defect or in combination with other defects, with special focus on APC resistance.The study cohort included 1192 consecutive patients with a history of clinically or objectively diagnosed venous and/or arterial thromboembolism and/or positive family history who were referred to our department for thrombophilia investigation from 02/1988 to 03/1997. All available family members of patients with plg deficiency were tested for plg, APC resistance and other thrombophilic defects that were established in the propositus.23/1192 propositi were plg-deficient corresponding to an overall prevalence of 1.9%, i.e. 2.2% in patients with venous thrombosis and 1.4% in those with arterial events. Out of the 23 plg-deficient propositi, 8 showed one or multiple additional thrombophilic defects, and in 4 patients relevant circumstantial risk factors were present. Of the 53 available family members, 28 were plg-deficient including 5 with additional APC resistance, and 4 subjects had isolated APC resistance. Ten of the 53 family members had already suffered thromboembolic events, i.e. 5 (18%) in the plg-deficient group and 5 (20%) in the non-deficient group, both groups showing an almost identical median age at the time of investigation (28.9 years and 27.1 years, respectively).Based on our data, plg deficiency is a rare defect in thrombophilic patients and as a single defect it does not seem to be a strong thrombotic risk factor, as 11 of 23 propositi had additional thrombophilic defects or circumstantial risk factors, and in the family members thrombotic events were equally frequent in the plg-deficient and non-deficient subjects.